“Mother and son: Reality versus art in virtual reality. Staging an atmospheric performance with immersive technologies” - Maxime Le Calvé (Ambiances)
Picture yourself spending several years studying the artistic activity of a famous contemporary artist. Someday you are told that the artist, Jonathan Meese, is going to produce a work in virtual reality (VR) for the ARTE channel and one of Berlin’s leading institutions specializing in immersive artworks, the Berliner Festspiele. In this piece, he will stage his creative process and the intimate sphere of his relationship with the person who puts him to work: his own mother. This performance, filmed in 360° by an expert technical team, is a perfect opportunity to take a lesson in sensory documentation as well as an exploration of the possibilities offered by this emerging medium. The production team commissioned me to do a series of ethnographic drawings about the production process of this work. Through these images, I depict the process of staging the performance. In this article, I describe a theatrical object “in the making.” In the last part, I highlight the specific component related to VR devices in this performance and the mediating effect that this technology imposes on it. This will allow me to show how the production process and the atmospheric dimension of the phenomenon are closely intertwined, and what immersive media can contribute to contemporary thinking on atmospheres in anthropology — and to the topic of ethnographic drawing.